What explains the success of emerging Asia's service exporters? - Andrea Ariu; Katariina Nilsson-Hakkala (Asian Development Bank (ADB), 2025)
This paper examines the determinants of service exports in emerging Asian economies, with particular emphasis on digital services, which have experienced considerable expansion across the region. Utilizing a structural gravity model, the findings indicate that supply-side factors predominantly drive service exports growth, rather than demand factors or trade policies. An indepth analysis of these supply-side factors underscores the pivotal role of human capital, specifically education and English proficiency, in bolstering exports, especially within the region's digital business process services sector. Further evidence reveals that stringent regulatory environments and barriers to digital infrastructure considerably impede exports in sectors such as telecommunications, computer and information services, and other business services. Conversely, enhanced internet connectivity not only increases exports of digital services but also boosts the exports of non-digital services.
Keywords: F10; F14; L80; 330; Asia; emerging economies; trade in services; digital services